Relationship between Food Calories Intake and Lung Function in Pedicab Drivers in Surabaya City - Amelia Lorensia; Rivan Virlando Suryadinata; Reza Dwi Anggrealdi; I Nyoman Yoga Diputra (Faculty of Public Health, Hasanuddin University, Makassar, 2023)
The increasing number of motor vehicles will increase the exposure of air pollution. Air pollution can cause respiratory disorders, especially on pedicab drivers who are working. Respiratory disorders are one of the diseases that can reduce quality of life and one of the risk factors of respiratory disorders is malnutrition. The purpose of this study was to determine the calorie intake of pedicab drivers with and without lung function impairment. This study uses analytical cross-sectional study, correlational study by using purposive sampling. Variables include: food calorie intake with 24-hour recall method. Respondents in the study consisted of 112 respondents in lung function impairment group (60 people (53.57%) had a deficit level of food calorie intake) and 11 respondents without the impairment group (5 people (45.45%) had a deficit level of calorie intake). The average types of food that were consumed by lung function impairment group are rice, tofu, tempeh, eggs, and sambal. There was no significant difference (p>0.05) between each item consumed by respondents. There was no significant difference of the effect of calories between the two groups (p>0.821). Therefore, it can be concluded that low intake of calories can be related to lung function, although further research is still needed regarding the relationship.